2016
DOI: 10.1002/ijc.30522
|View full text |Cite
|
Sign up to set email alerts
|

Dietary trace element intake and liver cancer risk: Results from two population‐based cohorts in China

Abstract: Dietary factors have been hypothesized to affect the risk of liver cancer via various mechanisms, but the influence has not been well studied and the evidence is conflicting. We investigated associations of dietary trace element intake, assessed through a validated food frequency questionnaire, with risk of liver cancer in two prospective cohort studies of 132,765 women (1997–2013) and men (2002–2013) in Shanghai, China. The associations were first evaluated in cohort studies and further assessed in a case-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 36 publications
1
27
2
Order By: Relevance
“…In the two cohorts of Shanghai Men's and Women's Health Study with 132 765 Chinese adults and over 500 liver cancer cases, it suggested that dietary Mn intake was inversely associated with liver cancer risk (highest v. lowest quintile, HR 0•51, 95 % CI 0•35, 0•73; P trend = 0•001) (80) . This result was repeated in a nested casecontrol subset that adjusted for HBV infection (80) .…”
Section: Dietary Trace Elements and Vitaminsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the two cohorts of Shanghai Men's and Women's Health Study with 132 765 Chinese adults and over 500 liver cancer cases, it suggested that dietary Mn intake was inversely associated with liver cancer risk (highest v. lowest quintile, HR 0•51, 95 % CI 0•35, 0•73; P trend = 0•001) (80) . This result was repeated in a nested casecontrol subset that adjusted for HBV infection (80) .…”
Section: Dietary Trace Elements and Vitaminsmentioning
confidence: 99%
“…lipid peroxidation, DNA and protein damage) (88) which may generate reactive oxygen species and oxygen-free radicals, thereby relates to carcinogenesis (89) . Nonetheless, given the limited existing observational studies, all of which were conducted in China (high-risk country) except a cohort study in Finland (86) , and multiple comparisons among those studies (80,83) , more related studies, especially studies in low-risk countries (e.g. European or Northern American countries) are warranted.…”
Section: Dietary Trace Elements and Vitaminsmentioning
confidence: 99%
“…Two nested case–control studies within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort have observed that serum zinc levels were inversely and copper/zinc ratio was positively associated with risk of HCC and colorectal cancer, whereas higher serum copper levels were associated with increased risk of colorectal cancer, but not with risk of HCC . However, findings from the Shanghai Women's Health Study (SWHS) and the Shanghai Men's Health Study (SMHS) showed no association between dietary intake of copper and zinc and liver cancer risk . With regard to cancer progression, data from a French cohort study and the National Health and Nutrition Examination Survey (NHANES) have linked higher serum levels of copper and lower zinc with increased overall cancer mortality .…”
Section: Introductionmentioning
confidence: 99%
“…20,21 However, findings from the Shanghai Women's Health Study (SWHS) and the Shanghai Men's Health Study (SMHS) showed no association between dietary intake of copper and zinc and liver cancer risk. 22 With regard to cancer progression, data from a French cohort study and the National Health and Nutrition Examination Survey (NHANES) have linked higher serum levels of copper and lower zinc with increased overall cancer mortality. 23,24 However, to date, epidemiological studies focusing on the role of copper and/or zinc imbalance in the prognosis of HCC, are still scarce in the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the common malignant tumors in China, hepatocarcinoma shows an increasing incidence rate and the age of onset is also becoming increasingly younger. Surgical resection is the most important treatment of early non-metastatic hepatocarcinoma, but the 5-year recurrent rate is still higher than 60% after surgery ( 1 ). Resistance to chemotherapy drugs is the main reason for poor prognosis of hepatocarcinoma.…”
Section: Introductionmentioning
confidence: 99%